Studies on physio-morphology, floral biology and fruit characteristics of mango (Journal of the Bangladesh Agricultural University, 2012)
Plant, inflorescences and fruit characteristics of 60 mango genotypes were studied during the period 2007 to 2008.  There were distinct variations among the findings of the gemplasm on plant, leaf, inflorescence fruit characters and  yield. Wide variations were observed in relation to the % flowering shoot, % perfect flower, % fruit set per panicle,  number of harvested fruits per plant, individual fruit weight, % edible portion and % total soluble solid ranging from  24.00 to71.33%, 8.10 to19.17%, 9.07 to 29.27%, 21.33 to 60.33, 365.33 to 219.00g, 45.22 to 79.83% and 16.90 to  28.26%, respectively. The germplasm MI28 was top of the list in case of number of panicle, number of main branch  per panicle, percent perfect flower and fruit harvest per plant. The maximum and minimum number of fruit set per  panicle was noted in MI28 and MI92, respectively. The maximum percentage of fruit harvest per panicle was found in  MI94 (5.46) but the germplasm MI28 gave the highest number of fruit per plant (60.33). Moreover, the germplasm  MI09 had the highest percentage of edible portion (79.83).   DOI: http://dx.doi.org/10.3329/jbau.v9i2.10985   J. Bangladesh Agril. Univ. 9(2): 187199, 2011